The Business of Commercial Legal Advice and the Ethical Implications for Lawyers and Their Clients - Mescher, Barbara Robin (Journal of business ethics, 2008)
Company directors and executives seek legal advice outside the company on a regular basis. This advice is meant to be given within the context of the lawyers’ professional obligations and ethical practise. What clients may not appreciate is there is often a conflict of interest between the lawyers’ professional and ethical concerns and the legal advice business. If lawyers follow their business interests, their advice may be incomplete especially in relation to the ethical consequences of that advice. This could lead to a compromise of the clients’ commercial interests and even raise doubts in relation to the legality of the clients’ proposed course of action.